2012
DOI: 10.1136/jmedgenet-2011-100520
|View full text |Cite
|
Sign up to set email alerts
|

AnSNX10mutation causes malignant osteopetrosis of infancy

Abstract: Background Osteopetrosis is a life-threatening, rare disorder typically resulting from osteoclast dysfunction and infrequently from failure to commitment to osteoclast lineage. Patients commonly present in infancy with macrocephaly, feeding difficulties, evolving blindness and deafness, and bone marrow failure. In w70% of the patients there is a molecularly defined failure to maintain an acid pH at the osteoclast-bone interface (the ruffled border) which is necessary for the bone resorptive activity. Methods a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
81
1
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(89 citation statements)
references
References 15 publications
(15 reference statements)
2
81
1
4
Order By: Relevance
“…(4) On this basis, we reasoned that SNX10 could be considered a good candidate gene associated with ''Västerbottenian osteopetrosis'' as well as in other cases of ARO with an unknown molecular defect.…”
Section: Introductionmentioning
confidence: 99%
“…(4) On this basis, we reasoned that SNX10 could be considered a good candidate gene associated with ''Västerbottenian osteopetrosis'' as well as in other cases of ARO with an unknown molecular defect.…”
Section: Introductionmentioning
confidence: 99%
“…73,74 Additional studies in other cell types or organisms have shown that SNX10 is interacting with the V-ATPase complex and may be important for its proper localization. 75 The protein kinase C-delta (PKCδ) seems to be an important and specific regulator of cathepsin K exocytosis in osteoclasts.…”
Section: Regulation Of Lysosomal Function In Osteoclastsmentioning
confidence: 99%
“…Klinik formuna bağlı olarak insidansı 1/20000 ile 1/250000 arasındadır. Otozomal resesif tipi, erken çocuklukta klinik veren en sık görülen ağır formdur (1)(2)(3). Anormal osteoklast aktivitesi normal kemik formasyonunu bozar ve sklerotik, frajil kemik oluşumuna neden olur.…”
Section: Introductionunclassified
“…Kemik dansitesinin artışı medüller kaviteyi daraltarak ekstramedüller hematopoez, hepatosplenomegali, anemi ve trombositopeniye yol açar. Büyüme geriliği ve tekrarlayan enfeksiyonlar sıktır (1,2,7). Hastalık fatal seyir-lidir.…”
Section: Introductionunclassified